2016
DOI: 10.21037/atm.2016.05.49
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genotype distribution of human papillomavirus among Hakka women in China

Abstract: Background: Human papillomavirus (HPV) infection is the primary risk factor for cervical cancer. HPV genotypes are associated with varying degrees of pathogenicity. To better formulate strategies for cervical cancer prevention, we investigated the population-specific distribution of HPV genotypes, including those with high carcinogenicity. Results: Risk stratification based on genotypes indicated that the prevalence of overall, high-risk, and low-risk HPV infections was 12.27%, 14.20%, and 0.79%, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
4
4
0
Order By: Relevance
“…Among the patients infected with multiple subtypes, co-infections with two HPV types was most common with percentage (76.04 %) in our population, which was comparable to the regional results of Guangzhou, Sichuan, and Macao in China from the previous reports (29)(30)(31). Many epidemiologic researches found that infection with multiple HPV genotypes seemed to increase the risk of developing the tissue abnormalities or high-grade lesions that precede invasive cervical cancer considerably, because HPV types might interact synergistically, which might contribute to increase the baseline risk observed with single-type infections (27,32).…”
Section: Discussionsupporting
confidence: 90%
“…Among the patients infected with multiple subtypes, co-infections with two HPV types was most common with percentage (76.04 %) in our population, which was comparable to the regional results of Guangzhou, Sichuan, and Macao in China from the previous reports (29)(30)(31). Many epidemiologic researches found that infection with multiple HPV genotypes seemed to increase the risk of developing the tissue abnormalities or high-grade lesions that precede invasive cervical cancer considerably, because HPV types might interact synergistically, which might contribute to increase the baseline risk observed with single-type infections (27,32).…”
Section: Discussionsupporting
confidence: 90%
“…The available data showed that the prevalence of HPV infection in Guangzhou, Shenzhen and Chaozhou was 10% [ 29 ], 18.4% [ 30 ] and 12.6% [ 31 ], respectively. Meanwhile, a latest study reported that the HPV prevalence in Hakka women in Heyuan City which is not far away from Meizhou is 12.27% [ 32 ]. Several risk factors contribute to the prevalence of HPV, like genetic variation, sexual behavior and biological predisposition [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism underlying the relation between HPV infection and age remains unclear. A possible reason may be that the women of these ages have a lower level of hormone as well as weaker immune function and therefore less capable to resist HPV infection [ 32 ]. Also, younger women that shortly after becoming sexually active are susceptible to HPV infection because they don’t know how to protect themselves [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the genotypes distribution in previous study reported by Miura et al [23], genotypes distribution in SCC and ADC in this study was similar, in which top three most common HPV genotypes were HPV16 (60.24%), HPV52 (8.10%) and HPV58 (8.10%) in SCC, and HPV18 (22.95%), HPV16 (21.34%) and HPV52 (14.34%) in ADC. HPV typespecific distribution has been investigated to be various from different regions in China [9,24,25], HPV16, HPV52, HPV58 and HPV18 have been reported to be most frequent genotypes in Chinese Hakka women [13,26]. Hence, the results in current study indicate the important role of HPV16, HPV18, HPV52 and HPV58 in causing CIN2/3 and ICC in Chinese Hakka women.…”
Section: Discussionmentioning
confidence: 58%